Aksi Lingkungan Untuk Pencegahan Demam Berdarah Dengue di Pekayon Jaya Bekasi Selatan - Sitorus, Helena; Firmansyah, Aldi Rizki; G, Danangjaya Dwi N.; Fauzy, Deny Rizky; Anjani, Rijal; Sukreni, Tulus (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
This community service program was carried out in Pekayon Jaya, South Bekasi, as an effort to support dengue fever prevention through environmental-based actions. The program aimed to increase public awareness, improve environmental hygiene, and strengthen community participation in reducing mosquito breeding sites. The activities consisted of three main programs: environmental clean-up, 3M (Drain, Cover, Reuse) socialization, and the construction of a centralized waste station. The environmental clean-up activity successfully improved the condition of drainage channels and cleanliness of the neighborhood with active participation from residents. The 3M socialization increased residents’ understanding of dengue prevention and encouraged behavioral changes in managing water containers and potential mosquito breeding sites. Meanwhile, the construction of a centralized waste station provided a structured waste disposal facility that helped reduce scattered waste and supported waste segregation practices. Overall, the program demonstrated positive impacts on environmental quality and community engagement. These activities are expected to encourage sustainable environmental health practices and support continuous dengue prevention efforts in Pekayon Jaya.